Study of Probiotic advantages for Chickens Raised without Antibiotics: A Comparative Analysis of Probiotics and Antibiotics in Poultry Nutrition (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Most emerging countries rely heavily on revenue from the poultry industry.There's a longhistory of using antibiotics to encourage growth. They help birds develop a stronger immune system andfight off sickness, and they also boost growth. Immunocompetence is defined as the capacity of anorganism to mount a proper immunological response in reaction to antigen exposure. Since the 1940s,they have been widely implemented as feed additives in the industry of animal agriculture. It has beenhypothesised that this impact arises from a complex biological relationship with intestinal microflora.The use of antibiotics as supplements in animals for the purpose of disease prevention and, in someinstances, efficiency improvement, was legalised by the Food and Drug Administration in the US in 1951.Yet, antibiotic use can lead to drug-resistant microorganisms. As a result, antibiotic use has beenreduced in favor of nutritional supplements like probiotics, which have been shown to have beneficialeffects on growth and the immune system.This review paper compares the use of probiotics in chickensfeed to the use of antibiotics, explains how probiotics work, and the cost-effectiveness of include themin poultry nutrition.